2013
DOI: 10.1021/jf401976e
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Competitive Indirect Enzyme-Linked Immunosorbent Assay Based on Monoclonal Antibodies for the Detection of 2-Dodecylcyclobutanone in Irradiated Beef

Abstract: A highly sensitive and specific competitive indirect enzyme-linked immunosorbent assay (ciELISA) based on monoclonal antibodies was developed for the detection of 2-dodecylcyclobutanone (2-DCB), a chemical marker for irradiated lipid-containing foods. 2-Oxocyclobutane undecanoic acid was used as an alternative to 2-DCB and conjugated to BSA and OVA via a conventional carbodiimide condensation reaction to prepare the immunogen and the coating antigen for 2-DCB. The monoclonal antibody against 2-DCB was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Given that the interior buried linear and conformational epitopes of the native molecule are mainly hydrophobic amino acid residues, more IgG and IgE epitopes were exposed on the molecule surface as the dose was increased. 36 The exposed epitopes were destroyed severely by irradiation, resulting in a decrease in IgG-and IgE-binding ability of the irradiated α-La. Previous studies have confirmed that irradiation treatment could destroy linear and conformational epitopes by denaturation, aggregation, fragmentation, and amino acid modification of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the interior buried linear and conformational epitopes of the native molecule are mainly hydrophobic amino acid residues, more IgG and IgE epitopes were exposed on the molecule surface as the dose was increased. 36 The exposed epitopes were destroyed severely by irradiation, resulting in a decrease in IgG-and IgE-binding ability of the irradiated α-La. Previous studies have confirmed that irradiation treatment could destroy linear and conformational epitopes by denaturation, aggregation, fragmentation, and amino acid modification of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, high-performance liquid chromatography , and liquid chromatography-tandem mass spectrometry (LC-MS/MS) have been widely used to measure the macrolide antibiotic residues in various foods of animal origin. , These methods are typically labor-intensive, time-consuming, and require sophisticated instruments; thus, they are unsuitable for screening large numbers of samples . However, immunoassays, especially enzyme-linked immunosorbent assays (ELISA), have been confirmed as alternative screening methods for rapid analysis , without some of the limitations of chromatographic methods. , The ELISA method could simply and reliably provide high sample throughput, sensitivity, and selectivity. , To the best of our knowledge, no other reports have yet been published concerning the development of an immunoassay to detect SP residues in food. In this paper, we detail the production of highly specific mAbs and the development of an icELISA to screen for SP residues in milk without requiring complicated sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, immunoassays, especially enzyme-linked immunosorbent assays (ELISA), have been confirmed as alternative screening methods for rapid analysis 15,16 without some of the limitations of chromatographic methods. 17,18 The ELISA method could simply and reliably provide high sample throughput, sensitivity, and selectivity. 19,20 To the best of our knowledge, no other reports have yet been published concerning the development of an immunoassay to detect SP residues in food.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The microplate luminometer was a Centro XS3 LB 960 (Germany). Chromatophores containing F 0 F 1 -ATPase, biotinylated e-subunit monoclonal antibodies, ATP synthesis buffer, and biotinylated 2-DCB monoclonal antibodies were prepared according to previous study (Zhao, Wang, Li, & Ha, 2013;. All other analytically purified reagents were purchased domestically.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%